Literature Review - Sustained Release In Liposom Technology On Emulsion Cream Curcumin For Burns - Adiwidjaya Kusuma, Gregorius; Aulia , Ayu; Lumayung , Censa; Kurnia Enggolan, Cahaya; Busdha , Desti; Maulana Akbar, Fatwa; Gloria, Fransisca (STIKES Telogorejo Semarang, 2023)
Preface : Burns is an injury on tissue caused by overexposure to flame, steam, hot liquid, chemist substances, electrical objects and radiant. Burns are classified based on its region and degree. One of the most important factors that affect the process of burns treatment is the prevention of burns infection. Turmeric is a natural resource that may be used. Its extract helps to haste re-epithelialization, cell proliferation and collagen synthesis. Proper sustain to improve the therapy is topical sustain. Liposom is one of topical sustains which is developed in pharmacy to increase efficacy. One of the efforts is to reduce the size of particles by sonication. Purpose : This research is literature review by finding national and international journals as database. Method : Literature review is done based on inclusion requirements like journals which discuss liposom sustain in form of cream for burns, original research from 2011 until 2022, and pre-clinical or clinical research journals. Result : Based on the findings, there are 5 journals that fulfill the inclusion requirement. There are two google-scholar journals and three Pubmed journals. Analysis of journal includes the effectiveness of liposom sustain in emulsion cream to treat burns. Conclusion : Curcumin increases the growth of beta factor, stimulates angiogenesis and accumulates extracellular matrix so these factors may treat burns.